ANALISIS PENGUKURAN KINERJA DENGAN PENDEKATAN VALUE FOR MONEY - Rai Dwi Andayani W. (UNHI Press, 2019)
This research intends to determine the performance of irrigation physical activiies of Badung Regency in 2018 based on: 1) economy ratio, 2) efficiency ratio, and (3)effectiveness ratio. This research is a descriptive by analyzing progress report of Irrigation project in Badung Regency in 2018. Data collection method is documentation and Data analysis tool is value for money concept. The results of the research concludes that the performance of Public Work Office on irrigation physical activity in Badung Regency in 2018 has been: 1) economically with economy ratio averagely under 100%; 2) efficiently conducted with efficiency averagely under 100%; 3) effectively conducted with effectivenessration of 100% in average.